2017
DOI: 10.1136/bmj.j4008
|View full text |Cite
|
Sign up to set email alerts
|

AMSTAR 2: a critical appraisal tool for systematic reviews that include randomised or non-randomised studies of healthcare interventions, or both

Abstract: The number of published systematic reviews of studies of healthcare interventions has increased rapidly and these are used extensively for clinical and policy decisions. Systematic reviews are subject to a range of biases and increasingly include non-randomised studies of interventions. It is important that users can distinguish high quality reviews. Many instruments have been designed to evaluate different aspects of reviews, but there are few comprehensive critical appraisal instruments. AMSTAR was developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
5,404
0
160

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 6,218 publications
(6,110 citation statements)
references
References 56 publications
13
5,404
0
160
Order By: Relevance
“…AMSTAR was published in 2007,24 and has been widely used for assessing methodological quality of systematic reviews25–27 of both Cochrane and non-Cochrane overviews of healthcare interventions 28. AMSTAR was recently updated to AMSTAR 2, and now consists of a 16-item online tool for evaluating systematic reviews as high, moderate, low or critically low of methodological quality 24.…”
Section: Methodsmentioning
confidence: 99%
“…AMSTAR was published in 2007,24 and has been widely used for assessing methodological quality of systematic reviews25–27 of both Cochrane and non-Cochrane overviews of healthcare interventions 28. AMSTAR was recently updated to AMSTAR 2, and now consists of a 16-item online tool for evaluating systematic reviews as high, moderate, low or critically low of methodological quality 24.…”
Section: Methodsmentioning
confidence: 99%
“…(14) Did the review authors provide a satisfactory explanation for, and discussion of, any heterogeneity observed in the results of the review? (15) If they performed quantitative synthesis did the review authors carry out an adequate investigation of publication bias (small study bias) and discuss its likely impact on the results of the review? (16) study may be cited only in one bibliographic database, the literature search must comprise multiple databases [3,10].…”
Section: Discussionmentioning
confidence: 99%
“…The methodological quality was assessed using the instrument "A MeaSurement Tool to Assess systematic Reviews" 2 [15]. The instrument consists of 16 domains assessing the risk of bias that may have arisen through poor conduct of the systematic reviews of both randomized controlled clinical trials and non-randomized studies [15].…”
Section: Data Extraction and Quality Assessmentmentioning
confidence: 99%
“…Recently, an update of the AMSTAR has been published (AMSTAR 2). This update is based on sixteen items and has an overall rating based on weaknesses in critical domains (54) . A new tool for assessing the risk of bias in systematic reviews (the ROBIS tool) mainly covers research questions relating to effectiveness, aetiology, diagnosis and prognosis (55) .…”
Section: Credibility Of the Evidence Within Meta-analysesmentioning
confidence: 99%